Study of effects of antiepileptic therapy on various biochemical and hematological parameters patients suffering of epilepsy - Bhosale, Uma A.; Loharkar, Neha R.; Yegnanarayan, Radha; Quraishi, Nilofar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Low therapeutic index of established antiepileptic drugs (AEDs) coupled with better understanding of the pathophysiology of seizure has encouraged the development of several novel AEDs. The conventional antiepileptics like phenytoin, phenobarbitone, valproate and carbamazepine and newer antiepileptics like levetiracetam, lamotrigine and topiramate etc. are used for epilepsy. AEDs induce potentially toxic effects over a period of time which remains undetermined over very long time. Earlier studies in this regard, states uneven results about biochemical (i.e. blood sugar level, lipid profile) and hematological (Hb%, blood cell count etc.) toxicity of AEDs. Aims: To unveil the toxic effects of AEDs when given singly or as combinations. Methods: Adult epileptics of either sex taking antiepileptic monotherapy or combination therapy for ≥ six months were enrolled. Biochemical and hematological parameters studied were compared with their age and sex matched controls, baseline and amongst groups. Statistical Analysis Used: Student’s ‘t’-test & One way ANOVA followed by posthoc Tukey HSD test for pair wise comparison; p<0.05 was considered significant. Results: Conventional antiepileptic combination therapy was found more toxic; p<0.01 for lipid profile. Combination groups showed significant reduction in Hb% (p<0.05) with no significant difference among them (p>0.05). Monotherapy and conventional combination therapy caused significant reduction in platelet count (p<0.01), but conventional combination therapy was found more toxic in this regard (p<0.05). Conclusions: Monotherapy found less toxic with no significant effects on lipid profile, Hb%, RBC count and O2 carrying capacity and less impact on platelets while combination therapy did not show any advantage over monotherapy and its use must be reserved only for refractory cases.